Relationships between restaurant attachment, experiential relationship quality and experiential relationship intentions: The case of single friendly restaurants in Taiwan. (September 2019) - Wu, Hung-Che; Cheng, Ching-Chan; Ai, Chi-Han; Chen, Guowei
Abstract: This study aims to examine the relationships between the restaurant attachment dimensions, the experiential relationship quality dimensions and experiential relationship intentions. A convenience sample of 492 single customers who dined at one single friendly restaurant in Taipei City of Taiwan was surveyed. The results will assist single friendly restaurant management in developing and implementing market-orientated service strategies to increase perceptions of restaurant dependence, restaurant identity, restaurant affect, restaurant familiarity and experiential relationship intentions in order to enable single customers to come to trust and feel satisfied with and committed to single friendly restaurants.